Effect of Feeding Different Dietary Levels of Rice Distiller’s Dried Grains with Solubles (RDDGS) on Growth Performance of Commercial Broiler Chicken - N Patel, Apal; S Joshi, Rajesh; P Savaliya, Fulabhai; B Patel, Atul; J Bhagora, Nikesh; R Devalia, Bharat (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A by-product of ethanol manufacturing, Rice Distillers Dried Grains with Solubles (RDDGS), is utilized as an alternate protein source in poultry diets. The current investigation was carried out over a duration of six weeks to examine the effect of feeding different dietary levels of RDDGS on growth performance of commercial broiler chicken. A total of 144 straight-run day-old commercial broiler chicks were randomly distributed to six treatments. Each treatment group consisted of four replicates and in each replicate, six chicks were there, leading to 24 chicks per treatment. The experimental diets consisted of Control basal diet (T1), and the diets T2 to T6 with 5, 10, 15, 20 and 25% RDDGS, respectively. The body weight of birds fed basal diet (T1) was significantly (p<0.05) higher than all the treatment groups, followed by basal diet with 5% RDDGS (T2). Body weights in treatments T3, T4, and T5 were significantly (p<0.05) lower, while basal diet with 25% RDDGS (T6) had the lowest body weight. Basal diet (T1) showed significantly (p<0.05) higher BWG than all other treatment groups. Birds fed basal diet with 5% RDDGS (T2) had significantly (p<0.05) higher BWG than those fed with T3, T4, T5 and T6 diet, but was significantly (p<0.05) lower than T1 diet. There were no significant differences in mean feed consumption between birds fed the T3, T4, T5 and T6 diets. However, the highest feed consumption was observed in T1 followed by T2, T5, T4, T3 and T6 diets. Overall FCR was significantly (p<0.05) better in T2 and T3 treatment groups as compared to control diet. The highest return over feed cost was obtained in the T2 diet as compared to other dietary groups. Beneficial effects on performance were noted at the lower level of 5% RDDGS in the diet. Hence, it can be concluded that RDDGS can be incorporated in broiler ration at the levels of 5%.